Direct identification of anatomical landmarks to locate second mesiobuccal canal of maxillary first molars: an in-vitro study - Ismail, Muhammad Bazli; Mohd Arifin, Muhammad Afiq Aiman; Mat Daud, Muhamad Sharifuddin; Che Musa, Muhd Firdaus (2020)
Introductions: Locating second mesiobuccal canal of permanent maxillary first molar tooth is always challenging for the clinician. Most of the time the orifice of the canal is covered by the dentin or has become calcified. Searching the canal in correct location will facilitates treatment and also can avoid complication such as perforation. Availability of reliable anatomical landmark will help clinician to locate MB2 canal in more predictable way. The objectives of this study are to locate the position of MB2 canal and investigate the correlation of the canal with surrounding anatomical structure. Materials and methods: Thirty extracted permanent maxillary first molar teeth with socio-demographic data were collected at Oral Surgery Clinic Kulliyyah of Dentistry IIUM Kuantan and private dental clinic around Kuantan. A standard rhomboidal access cavity was prepared and all canals were located either under direct eye vision or with the aid of dental loupe (3.5x magnification). Ultrasonic tip or LN bur was used to locate MB2 canal when necessary. The relationship of MB2 canal with another canal was examined and any potential landmark was recorded. Results: Second mesiobuccal canal was located in 80% of the total sample. About 93.3% of the located canal was on the opposite location of DB canal which is parallel with straight mesio-distal line on the palatal tooth surface at the cervical area. The mean of interorifice distance between MB1 and MB2 was 1.3mm. The MB2 canal was always located mesial or directly on the MB1-palatal line. There was no significant association between the position of MB2 with socio-demographic factors (gender and ethnicity). Conclusions: The palatal surface of the permanent first maxillary molar can serve as a reliable anatomical landmark in locating MB2 canal. By referring to a straight mesio-distal imaginary line on the palatal aspect at the cervical area, MB2 canal can be anticipated to be at the opposing direction of distobuccal canal. In addition, the canal is always located mesial to or directly on the MB1-palatal line and within 3mm palatal to MB1 canal.